2002
DOI: 10.1149/1.1510321
|View full text |Cite
|
Sign up to set email alerts
|

Using a Boron-Based Anion Receptor Additive to Improve the Thermal Stability of LiPF[sub 6]-Based Electrolyte for Lithium Batteries

Abstract: The possibility of using a strong anion coordinate agent, tris͑pentafluorophenyl͒ borane ͑TPFPB͒, to suppress the thermal decomposition of LiPF 6 -based electrolyte was studied. Cyclic voltammogram measurements showed that addition of 0.1 M TPFPB maintained electrochemical stability of a LiPF 6 -based electrolyte at 55°C for a week, while under the same conditions severe degradation in electrochemical stability was observed in the same LiPF 6 -based electrolyte without the TPFPB additive. A Li/LiMn 2 O 4 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 8 publications
0
70
0
Order By: Relevance
“…The most representative anion receptor is probably TPFPB (Figure 6, right-hand side), in which boron is extremelye lectron deficientd ue to the surrounding highly electron-withdrawing perfluorinated phenyl groups.I tw as demonstrated that the addition of ac ertain amount of TPFPB could significantly improve the electrochemical performance of LIBs [121] and the thermals tability of LiPF 6 -based electrolytes. [133,134] Nevertheless, it should be considered that an excess of TPFPB may have an egative impact on the thermals tability of the electrolyte for two reasons: 1) extensive depletion of the inorganic SEI components, such as LiF,p resumably resultsi navery thin and inhomogeneous SEI layer; and 2) extensive "scavenging" of fluorine anionsm ay favor the formation of the strong Lewis acid PF 5 by shifting the equilibrium in Equation (1) towards the right. As-generated PF 5 may then inducea ccelerated decomposition of the SEI through an acid-base reactionw ith the SEI components and degradation of the electrolyte.…”
Section: Sei Supporting Additivesmentioning
confidence: 99%
“…The most representative anion receptor is probably TPFPB (Figure 6, right-hand side), in which boron is extremelye lectron deficientd ue to the surrounding highly electron-withdrawing perfluorinated phenyl groups.I tw as demonstrated that the addition of ac ertain amount of TPFPB could significantly improve the electrochemical performance of LIBs [121] and the thermals tability of LiPF 6 -based electrolytes. [133,134] Nevertheless, it should be considered that an excess of TPFPB may have an egative impact on the thermals tability of the electrolyte for two reasons: 1) extensive depletion of the inorganic SEI components, such as LiF,p resumably resultsi navery thin and inhomogeneous SEI layer; and 2) extensive "scavenging" of fluorine anionsm ay favor the formation of the strong Lewis acid PF 5 by shifting the equilibrium in Equation (1) towards the right. As-generated PF 5 may then inducea ccelerated decomposition of the SEI through an acid-base reactionw ith the SEI components and degradation of the electrolyte.…”
Section: Sei Supporting Additivesmentioning
confidence: 99%
“…The electrolyte solution with lithium hexafluorophosphate (LiPF 6 ), which the current lithium-ion industry uses exclusively, shows thermal instability. Recently, Herstedt and McBreen et al reported that tris(pentafluorophenyl) borate (TPFPB) as an anion receptor improved the thermal stability of lithium ion cells containing LiPF 6 -based electrolyte solution [9][10][11]. It is believed that this behavior is obviously linked to Lewis acid-base interaction between boron atoms of TPFPB anion receptor and PF 6 − anions.…”
Section: Introductionmentioning
confidence: 99%
“…For the SEI formed with LiPF 6 -carbonate electrolyte, isolated LiF is the important factor producing unstable SEI [87]. For this reason, many boron-based anion receptors have been developed to dissolve LiF [88].…”
Section: Safety Concerns With LI Saltsmentioning
confidence: 99%